Survival Analysis Of Diabetes Mellitus Patients With Diabetic Ulcers - Nailah, Andi Nailah Amirullah; Anggraeni; Karmila Sukri (Journal of Islamic Nursing, 2024)
ABSTRACT Diabetes Mellitus (DM) is a chronic disease that occurs because the pancreas does not produce enough insulin or when the body cannot effectively use the insulin it produces. The general effects of uncontrolled diabetes can lead to serious complications over time. This study aims to determine the factors that influence the survival of diabetes mellitus sufferers with diabetic ulcers at RSUP Dr. Wahidin Sudirohusodo and Ibnu Sina Hospital, Makassar City. This research is an analytical observational study with a retrospective cohort design. The study population was all patients suffering from DM with diabetic ulcers and recorded in medical records. The research was carried out by tracing the medical records of 100 samples of DM sufferers with diabetic ulcers. Data were analyzed using Kaplan-Meier (p, 0.05) and Cox regression (p<0.25). The results of research with Kaplan Meier show that the factors that influence the survival of diabetes mellitus sufferers with diabetic ulcers are total cholesterol levels (p=0.000), HDL levels (p=0.004), triglyceride levels (p=0.011), and duration of DM ( p=0.000). From multivariate analysis using Cox Regression, the Hazard Ratio (HR) for total cholesterol levels = 11.441 and HR for long DM = 11.829. Avoiding risk factors can influence the survival probability of diabetes mellitus sufferers with diabetic ulcers at RSUP Dr. Wahidin Sudirohusodo and Ibnu Sina Hospital, Makassar City.   Keywords: Survival, Diabetes Mellitus, Diabetic Ulcer